PUTUSAN MAHKAMAH KONSTITUSI TENTANG PEMILU SERENTAK DIHUBUNGKAN DENGAN PENCEGAHAN KORUPSI POLITIK - Dedi Mulyadi; M. Rendi Aridhayandi (Jurnal Hukum Mimbar Justitia, 2015)
Given the importance of the elections in a democracy, the principle of keeping the elections in accordance Luber Jurdil, especially of political corruption. Then on January 23, 2014 the Constitutional Court passed a decision in a judicial review of Law No. 42 of 2008 on General Election of President and Vice President of the Constitution of the Republic of Indonesia Year 1945, by decision No. 14 / PUU-XI /2013 decided elections simultaneously at in 2019 and beyond. Concurrent elections is one of the prevention of political corruption. Political corruption is an act of power holders in order to take advantage of the power. For example: the financing of political parties, the purchase "ticket" or "boat" in local elections, as well as imaging and campaign costs. Constitutional Court decisions on the implementation of simultaneous elections in the year 2019 is one of the prevention of political corruption. The method used in this study using sociological juridical approach, specification of descriptive analysis. Identification of problems regarding (1) the background of the political corruption in the electoral operations, (2) the potential for problems in the implementation of elections simultaneously in 2019 can save and prevention of corruption of political, (3) attempts to resolve any potential problems in the elections simultaneously 2019 against the corruption of political purpose of this study is to know about the background of the political corruption, potential problems in the implementation of simultaneous elections and the efforts of its completion. The method used in this study is juridical sociological analysis with descriptive specification. The research result that the background of the political corruption is the ambition to achieve dynastic power, while the verdict was handed down too lightly, and the efforts made by the political financing system and raising the parliamentary threshold.Keywords : Political corruption, The Constitutional Court ruling, The elections simultaneously.